The optimization of turret location on FPSO in Malaysia seawater - Mohd. Yusof, Adibah Fatihah (2017)
As Malaysia has start deepwater oil exploration near offshore Sabah, more floating structures have been installed. However, less study has been conducted on FPSO with turret mooring system in Malaysia seawater, especially in offshore Borneo. Even though offshore Borneo is part of South China Sea, the environmental condition is milder and its exhibit strong current from depth 50m to 150m. Hence, the present study analyzed the influence of turret location to surge, sway, heave, pitch, roll and yaw motions effect on the FPSO Kikeh operating in Kikeh Field. A simulation on FPSO Kikeh with five different turret locations; turret at the bow, midship, 25%, 50% and 75% from the bow, in regular wave and collinear sea states have been done. From the analysis of the simulations, it is found that yaw motions become critical as turret distance from bow increases. Besides that, roll motion increases as yaw motion increases and this is due to the coupling effect. The turret at the bow is the most prefered for FPSO operating in Kikeh because it has the lowest structure excursion and lowest mooring lines tension. In addition, the environmental force exerted on the structure also low.